Metabolic reprogramming and prognostic modeling in pancreatic cancer: insights from WGCNA - Song, Zhuo; Sun, Zhijia; Di, Yupeng; Liu, Xu; Kang, Xiaoli; Ren, Gang; Wang, Yingjie (Frontiers in Genetics, 2025)
PurposeMetabolic reprogramming plays a crucial role in multiple malignant features of pancreatic cancer (PC). However, few studies have comprehensively examined metabolic features of PC and provided guidance for their treatment.MethodsThis study tried to identify metabolism-associated hub genes based on metabolic phenotypic levels through weighted gene co-expression network analysis, and constructed a risk model for PC, then verified its accuracy and explored the potential mechanisms.ResultsWe screened out five metabolic hub and prognostic genes (DLX3, HMGA2, SPRR1B, MYEOV, and FAM111B) and constructed a novel metabolism-associated gene signature to predict the prognosis of PC. The model was verified efficacy and demonstrated with good performance through analysis of Kaplan-Meier plotter, receiver operating characteristic curves, comparing with reported models, application in predicting drug sensitivity and constructing a nomogram model. Correlation analysis revealed a close association between the levels of risk score and DNA damage response (DDR, correlation coefficient: 0.41, P < 0.001). Enrichment analysis indicated that risk scores were derived from multiple metabolic or proliferative pathways, providing further evidence that metabolism may mediate DDR to affect PC survival.ConclusionThrough bioinformatics analysis, we identified five prognostic relevant differentially expressed genes highlighting the role of metabolism-associated factors in pancreatic cancer, which reveals a strong correlation ship with DDR, offering new insights into treatment strategies that combine metabolism with DDR.